Birefringence analysis of collagen supraorganization in cat corneas with tropical keratopathy - Tinasi, Ana L. S. N.; Silveira, Camila P. B. [UNESP]; Honsho, Cristiane S.; Laus, José L.; Aldrovani, Marcela [UNESP] (Wiley, 2023)
Objective: To evaluate the birefringent properties of the cornea and examine the supraorganizational aspects of collagen fibers in cats with tropical keratopathy. Procedure: In this study, 10-micrometer-thick sections of corneal tissue from cats with tropical keratopathy were examined, both in the opaque and transparent areas of the anterior stroma. Control samples were obtained from healthy cat corneas. Polarized light microscopy was employed to evaluate the birefringent properties using two distinct methods. The first method involved measuring the optical retardation associated with corneal birefringence, while the second method assessed the alignment/waviness of the birefringent collagen fibers. Differences were significant when p <.05. Results: Tropical keratopathy resulted in a significant rise (p <.05) in optical retardation in both opaque and transparent regions of the cat cornea. In the anterior stroma, both the opaque zones and transparent tissue exhibited a higher degree of collagen fiber packing than the control corneas. However, no significant differences (p >.05) in alignment were observed between the transparent tissue of the diseased cornea and the healthy corneas. Conclusion: Supraorganizational changes in collagen fiber packing are not restricted to lesion zones in cat corneas affected by tropical keratopathy. Such alterations also occur in the corneal tissue of the anterior stroma adjoining the lesions. Therefore, it is plausible that the transparent tissue of the anterior stroma in corneas affected by the disease may have functional abnormalities, despite its macroscopic healthy appearance. Additional investigations are required to clarify the implications of these potential defects and their conceivable contribution to tropical keratopathy.
Keywords: corneal defects; corneal opacity; extracellular matrix; feline; Florida spots; ophthalmology